Determination of Corporate Social Responsibility Disclosure Using Firm Size as a Moderation Variable in Palm Oil Companies - Yunarti Yunarti; Erlina Erlina; Khaira Amalia Fachrudin (Syntax Corporation Indonesia, 2023)
-